Cost Plus Pricing Method in Determining the Profit of Home Industry Sub Sector MSMEs in Tolitoli Regency. - Yanto, Edi; Wulandari, Putri; Rasyid, Moh.; Mustaring, Mustaring (STIE Mujahidin Tolitoli Development Economics Study Program, 2025)
This study aims to analyze the application of the cost plus pricing method in determining selling prices and profits in Micro, Small, and Medium Enterprises (MSMEs) in the home industry sub-sector in Tolitoli Regency, a case study on Tofu Tempe Sumali MSMEs. The cost plus pricing approach adds a certain profit margin to the total production cost as the basis for determining the selling price. Through a quantitative study on Sumalian Tofu Tempeh MSMEs, the results of the study found that the profit obtained on the selling price based on the cost plus pricing method was IDR 1,060,416,000 from the selling price of 7,364/package with a total production of 144,000 packages. This study found that business actors have not applied the price calculation method systematically, so they often set prices based on intuition or market prices that are not in accordance with the actual production cost. With the application of the cost plus pricing method, MSMEs can determine a more rational selling price and obtain more stable and sustainable profits.